Optimasi Perencanaan Menu Diet Bagi Penderita Penyakit Asam Urat Menggunakan Weighted Goal Programming - Fadhilla, Aisya; Ahmad, Defri (Journal of Mathematics UNP, 2024)
A low-purine diet is recommended for gout patients. The goal of this diet are to achieve and maintain normal nutritional status while also lowering uric acid levels in the blood. This study aims to manage the menu of a low-purine diet in order to minimize the deviations of energy, proteins, fats, and carbohydrates using the weighted goal programming method. The study was started by formulating the models and planning a diet menu using the weighted goal programming method. The results showed that the food portions of the low-purine diet menu planning using the weighted goal programming method could fulfill the target of the patient's total daily energy needs.